FLIPPED CLASSROOM AS A PEDAGOGICAL TOOL FOR DEVELOPING STUDENTS' INDEPENDENT METHODOLOGICAL TRAINING (Universal International Scientific Journal, 2026)
This article examines the flipped classroom model as a modern pedagogical tool aimed at developing independent methodological training for students of pedagogical universities. The relevance of the study is determined by the need to develop future teachers' abilities for autonomous learning, professional reflection, and independent methodological decision-making in the context of the transforming educational environment. The purpose of the article is to theoretically substantiate the didactic potential of the flipped classroom model and identify its potential for student methodological training. The research methods used include an analysis and synthesis of scientific and pedagogical literature, a comparative pedagogical analysis of traditional and flipped learning models, and a structural and functional analysis of the educational process. The flipped classroom promotes the activation of students' cognitive activity, the development of independent learning skills, and the development of critical and methodological thinking. The role of digital educational technologies in ensuring the individualization and flexibility of learning is substantiated. The main difficulties in implementing the flipped classroom model are identified, and pedagogical conditions for increasing its effectiveness in the system of higher pedagogical education are determined.